Ground/satellite observations and atmospheric modeling of dust storms originating in the high Puna‐Altiplano deserts (South America): Implications for the interpretation of paleo‐climatic archives - Gaiero, Diego Marcelo; Simonella, Lucio Esteban; Gassó, S.; Gili, Stefania; Stein, A. F.; Sosa, P.; Becchio, Raul Alberto; Arce, J.; Marelli, H. (Journal of Geophysical Research: Atmospheres)
This study provides a detailed description of the sources, transport, dispersion, and deposition of two major dust events originating from the high‐altitude subtropical Puna‐Altiplano Plateau (15?26°S; 65?69°W) in South America. A long and severe drought provided the right conditions for the onset of both events in July 2009 and 2010. Dust was transported SE and deposited over the Pampas region and was observed to continue to the Atlantic Ocean. Dust monitoring stations located downwind recorded both events, and samples were characterized through chemical and textural analysis. Through a combination of meteorological data and satellite observations (CALIPSO andMODIS detectors), we estimate the emission flux for the 2010 event. This estimate was used to constrain the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) transport model and simulate the dust event. Both satellite imagery and model results agree in the location and extension of the dust cloud. CALIPSO detected dust between ~6000 and ~8500 m a.s.l., which remained at this height during most of its trajectory. The dust cloud mixed with a strong convective system in the region, and the associated precipitation brought down significant amounts of dust to the ground. Dust particle size analysis for both events indicates that near the sources dust samples show median modes of 12.4?14.1 μm, similar to modes observed 1300 km away. Chemical composition of sediments from potential dust sources shows distinct signatures within the Puna‐Altiplano Plateau, the Puna sector being clearly different from the Altiplano area. In addition, both sources are markedly different from the Patagonian chemical fingerprint.These results have important implications to improve the interpretation of aleoenvironmental archives preserved on the Argentine loess, Antarctic ice cores, and Southern Ocean marine sediments. Fil: Gaiero, Diego Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Córdoba. Centro de ...